2014
DOI: 10.1186/1749-799x-9-11
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on sagittal plane profile of the lumbar spine according to standing, supine, and various sitting positions

Abstract: BackgroundThe sagittal alignment of the spine changes depending on body posture and degenerative changes. This study aimed to observe changes in sagittal alignment of the lumbar spine with different positions (standing, supine, and various sitting postures) and to verify the effect of aging on lumbar sagittal alignment.MethodsWhole-spine lateral radiographs were obtained for young volunteers (25.4 ± 2.3 years) and elderly volunteers (66.7 ± 1.7 years). Radiographs were obtained in standing, supine, and sitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 30 publications
2
54
3
Order By: Relevance
“…Additionally, the fact that most significant postural changes and higher incidence of IVD degeneration occurred at the inferior LS may be related to the greater forces acting on these levels through the LS (Alexander et al 2007, Pal andRoutal 1987). It has been previously suggested that in the presence of IVD degeneration at inferior levels a compensatory mechanism of increased lordosis occurs at superior lumbar levels (Lee et al 2014, Rodriguez-Soto et al 2013. However, in the present study, we did not find evidence of this phenomenon.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, the fact that most significant postural changes and higher incidence of IVD degeneration occurred at the inferior LS may be related to the greater forces acting on these levels through the LS (Alexander et al 2007, Pal andRoutal 1987). It has been previously suggested that in the presence of IVD degeneration at inferior levels a compensatory mechanism of increased lordosis occurs at superior lumbar levels (Lee et al 2014, Rodriguez-Soto et al 2013. However, in the present study, we did not find evidence of this phenomenon.…”
Section: Discussioncontrasting
confidence: 99%
“…Although these lumbopelvic parameters did not differ markedly from those in other reports [20], there is likely to be a discrepancy in lumbopelvic positional parameters between the standing and supine positions [21]. Thus, a future analysis of the relationship between standing spinal alignment and presence of SJVP is desirable.…”
Section: Discussionmentioning
confidence: 62%
“…Once disk degeneration has started local kyphosis and overload progressively increase, accelerating disk disruption [8]. We should also consider that most of these patients become paraplegic when they are young and in young patients the upper lumbar spine is very mobile [9] and this could be a further reason of disk quick degeneration in absence of muscular control. Nevertheless, the rarity of CSD compared to the number of patient submitted to spinal fusion following a SCI means that many other unknown factors and mechanisms must influence the onset of this pathology, so further studies are required to properly treat and prevent it.…”
Section: Discussionmentioning
confidence: 99%